menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Solve for x. 2(4x - 1) + 3(3 - 2x) = 0 x = -4 x = -7/2 x = -4/3 x = -7/6
asked
Sep 19, 2019
114k
views
3
votes
Solve for x.
2(4x - 1) + 3(3 - 2x) = 0
x = -4
x = -7/2
x = -4/3
x = -7/6
Mathematics
high-school
K M
asked
by
K M
5.7k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
1
vote
I'm positive that it is -7/2
Bert Levrau
answered
Sep 22, 2019
by
Bert Levrau
5.0k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
6
votes
The correct answer: x=-7/2
Hope this help!!!
Mike Richards
answered
Sep 25, 2019
by
Mike Richards
5.6k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.7m
questions
7.4m
answers
Other Questions
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Can someone help me with 5??? ASAP?
Solve for h 3h=7(2/7-3/7h)-10
185g in the ratio 2:3
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org